Analysis of Lawson Indonesia Product Sales in Participation: A Quantitative Study for the Period July-December 2024 - Salma Salsabila; Bagus Yunianto; Mellasanti Ayuwardani (JOBS (Jurnal Of Business Studies), 2025)
This study aims to analyze the influence of event categories on the sales of Lawson Indonesia's products. Amidst the intense competition in the convenience store industry, the effectiveness of event marketing strategies is crucial. This research employs a quantitative method using secondary data from 72 events Lawson participated in during the July-December 2024 period, selected through a saturated sampling technique. Data analysis techniques include validity test, reliability test, classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation), F-test, t-test, coefficient of determination, and multiple linear regression analysis using SPSS 25. The results show that both the number of visitors and event categories have a significant positive effect on sales. The Adjusted R Square value of 0.156 indicates that the independent variables explain 15.6% of the variation in sales, while the remaining 84.4% is explained by other factors not included in this research model